Implementasi K-Means pada Klasterisasi Jenis Disabilitas - Dwiana, Fadiah Irine; Utami, Wika Dianita; Hamid, Abdulloh; Sriasih (Jurusan Matematika FMIPA UNM, 2023)
Disability need assistance from the authorities to support the activities of persons with disability. Types of disability include physical disability, visual impairment, speech impairment and mental disorders. This study goal of this study to cluster disability per sub-district in Sidoarjo Regency by type of disability using the K-Means method. The data used is data on the number of disability in Sidoarjo Regency from January to August 2022. This cluster analysis produces four optimal clusters with the highest silhouette coefficient value of 0.33. The results of the analysis of this study formed 4 clusters in the first cluster, namely 4 sub-districts with a very high number of disability, the second cluster, namely 4 sub-districts with a high number of disabilitys, the third cluster only 1 sub-district with a moderate number of disabilitys, the fourth cluster, namely 5 sub-districts with a low number of disability.